Measurement of large angle fragments induced by 400 MeV n−1 carbon ion beams. (21st July 2015) - Aleksandrov, Andrey; Consiglio, Lucia; De Lellis, Giovanni; Di Crescenzo, Antonia; Lauria, Adele; Montesi, Maria Cristina; Patera, Vincenzo; Sirignano, Chiara; Tioukov, Valeri
Abstract: The use of carbon ion beams in radiotherapy presents significant advantages when compared to traditional x-ray. In fact, carbon ions deposit their energy inside the human body at the end of their range, the Bragg peak. Unlike x-ray beams, where the energy deposition decreases exponentially inside the irradiated volume, the shape of carbon beams is sharp and focused. Advantages are an increased energy released in the cancer volume while minimizing the irradiation to healthy tissues. Currently, the use of carbon beams is limited by the poor knowledge we have about the effects of the secondary fragments on the irradiated tissues. The secondary particles produced and their angular distribution is crucial to determine the global dose deposition. The knowledge of the flux of secondary particles plays a key role in the real time monitoring of the dose profile in hadron therapy. We present a detector based on nuclear emulsions for fragmentation measurements that performs a sub-micrometric tridimensional spatial resolution, excellent multi-particle separation and large angle track recognition. Nuclear emulsions are assembled in order to realize a hybrid detector (emulsion cloud chamber (ECC)) made of 300  μ m nuclear emulsion films alternated with lead as passive material. Data reported here have been obtained by exposing two ECC detectors to the fragments produced by a 400 MeV n −1 12 C beam on a composite target at the GSI laboratory in Germany. The ECC was exposed inside a more complex detector, named FIRST, in order to collect fragments with a continuous angular distribution in the range 47°–81° with respect to the beam axis. Results on the angular distribution of fragments as well as their momentum estimations are reported here.